HUBUNGAN LAMA PENGGUNAAN KONTRASEPSI DENGAN GANGGUAN SIKLUS MENSTRUASI PADA AKSEPTOR KB SUNTIK DI PMB HUSNIYATI - Saswita, Reni; Emilda, Sri; Agustin, Adilah (LPPM STIKes Mitra Adiguna, 2024)
Family planning (KB) is one of the largest and most important preventive health services. Through the family planning program, population growth will be controlled so that it can increase the level of health and welfare for families (Endang, 2018). The aim of this research is to determine the relationship between length of use and menstrual cycle disorders in injectable contraceptive acceptors in PMB in 2023. This research uses a quantitative descriptive method with a cross sectional approach with a sample size of 96 people. The results obtained from the bivariate analysis of the chi-square statistical test show that the p value = 1,247> a 0.05. Conclusion: There is no relationship between the length of contraceptive use and menstrual cycle disorders in injectable contraceptive acceptors at PMB Husniyati Palembang in 2023. Suggestions are expected for midwifery students and health workers can provide IEC through education or counseling about the benefits and side effects of effective contraceptives for the community and it is hoped that contraceptive users can always consult with health workers regarding changes that occur after using contraception so that if there are abnormalities they can be immediately diagnosed overcome.